Hubungan Lama Menderita Penyakit Kronis dengan Quality of life (Qol) pada Penderita Diabetes Mellitus di Puskesmas Banyumulek - Rahmani Rahmani; Hadi Suryatno; Ni Nyoman Santi Tri Ulandari; Sukardin Sukardin; Nurhayati Nurhayati (LPPM STIKES Mataram, 2023)
Introduction: Diabetes Mellitus is a micronic hyperglycemia condition accompanied by various metabolic disorders due to hormonal disorders which cause various chronic complications. One way to improve the quality of life is to carry out good management. Objective: This study aims to determine the relationship between the length of suffering from chronic disease and the quality of life of Diabetes Mellitus sufferers at the Banyumulek Community Health Center. Method: This type of research is quantitative research with descriptive correlation and a cross-sectional approach carried out on 96 samples of diabetes mellitus patients in the Banyumulek Community Health Center work area obtained using purposive sampling technique, and data collection using a questionnaire. Results: Research shows that the quality of life in diabetes mellitus patients at the Banyumulek Community Health Center is in the poor category, as many as 43 (44.8%) respondents. In the short term (<5 years) with Quality of life less than 2 (2.0%) respondents, in the medium term (5-10 years) with Quality of life less there were 26 (27%) respondents. The p value of 0.001 is smaller than α, namely (p<0.05). Conclusion: based on the results of this study, it can be concluded that there is a relationship between the length of suffering and the Quality of life in diabetes mellitus patients in the Banyumulek Community Health Center working area.